Garlic scape, an alternative food with human health benefits - Gonzalez, Roxana Elizabeth (2012)
Garlic (Allium sativum L.) has been used as a medicinal agent for thousands of years. Attributes like, antioxidant properties, heart disease prevention, including atherosclerosis, and also reduction of both plasma cholesterol level and blood pressure are reported for garlic consumption. Not only the mature bulbs, but also the leaves and scapes are used for various seasoning or edibles. In some areas garlic is produced particularly for its scapes. Under favorable conditions garlic may produce both, scapes and bulbs. There is an increasing demand for natural food with high added health value for worldwide human consumption. Thus, the main goal of this study was to determine in vitro antiplatelet activity and pungency of garlic scapes and bulbs. Two garlic cultivars: ‘Sureño INTA’ and ‘Gostoso INTA’ were chosen from the germplasm collection of INTA La Consulta. In vitro antiplatelet activity of bulbs and scapes was measured using whole blood electrical impedance aggregometry, whereas pungency was analyzed according to Schwimmer and Weston (1961). Bulbs of both garlic cultivars evaluated showed higher in vitro antiplatelet activity and pungency, than their scapes. Significant differences were found between scape pungency (P<0.05) but not among bulb pungency. Regarding in vitro antiplatelet activity, we observed differences between bulbs and scapes. ‘Sureño INTA’, showed the highest antiaggregatory effects. These results provide evidence about the potential of scape consumption as an alternative food with added health benefits.